Proceso de atención de enfermería en adulto mayor con fractura de cadera. - López Jiménez, Judy Azaria (2023)
This clinical case study addresses the application of the nursing care process in an adult patient over 93 years of age who, as a result of a fall, results in a right hip fracture. The methodology applied was through the Nursing Care Process (PAE) through the systematic and organized assessment oriented in the philosophical proposal of Marjory Gordon where a significant amount of relevant data of the person (physical, psychic, social, environment) was obtained, in an orderly manner, which in turn facilitated their analysis. The assessment was carried out through the collection of subjective, objective data, the review of the clinical history and reports of other professionals. As a consequence of the aging of the population, as well as the natural physiological changes of senile age, such as loss of agility, balance, strength, etc. There is an ease for falls. These falls cause fractures in a relatively high percentage, specifically between 5 and 10%. Through this study it was possible to determine that the risk increases mainly with age. The most outstanding thing about this situation is that trauma in the elderly requires a series of special attention and care. These people already have a diminished physiological reserve, have a compromised recovery capacity and frequently have associated diseases. Therefore, these fractures have a high morbidity and require prolonged periods of hospitalization. The study of this topic, therefore, is of substantial importance.